Research progress in Traditional Chinese Medicine treatment and nursing care of upper limb lymphedema after breast cancer surgery (乳腺癌术后上肢淋巴水肿中医治疗与护理研究进展) - LI Yajing (李亚静); CHEN Hong (陈宏) (中西医结合护理)
Breast cancer is one of the most common malignant tumors in women today. Surgical treatment is an important part of comprehensive treatment of breast cancer. Breast cancer-related lymphedema (BCRL) is a complication after breast cancer surgery. Traditional Chinese medicine combined with comprehensive nursing interventions has remarkable clinical effect in the treatment of upper limb lymphedema after breast cancer surgery. This paper reviews the research progress of common Traditional Chinese Medicine treatment and nursing technology of breast cancer-related lymphedema, and provides reference for improvement of quality of postoperative nursing of patients with breast cancer. (乳腺癌是当今女性最常见的恶性肿瘤之一, 手术治疗是乳癌综合治疗的重要内容。乳腺癌术后相关上肢淋巴水肿是乳癌术后并发症, 中医联合综合护理干预治疗乳腺癌术后上肢淋巴水肿临床效果明确。本文对乳腺癌术后相关上肢淋巴水肿的常用中医治法、护理技术研究进展进行综述, 旨在为提高乳腺癌术后护理质量提供参考。)